Subnational partnerships for sustainable development transatlantic cooperation between the United States and Germany - Ralston, Holley Andrea; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
'There is a growing body of literature that explores what drives subnational actors to become agenda setters on climate change, sustainability and other environmental matters. This book adds a new dimension to this literature by focusing on international environmental partnerships between states, such as those between Maryland and Schleswig-Holstein, Wisconsin and Bavaria, as well as California and North Rhine-Westphalia. In-depth case studies examine what drives these international partnerships, how they function, and what supports and inhibits their effectiveness. This book represents the most in-depth study that exists of international environmental policy agreements at the subnational level. It is an important addition to the field.' - Miranda Schreurs, Free University of Berlin, Germany. This fascinating volume examines the recent increase in subnational environmental policy agreements between different countries, with a particular focus on Germany and the US. Holley Ralston explores why international environmental partnerships are forming at the state level and the factors that both aid and inhibit their long-term success. The book begins with an in-depth analysis of the theoretical and historical frameworks of transnational partnerships, before transitioning into a discussion of specific environmental agreements between US and German states. The following partnerships are covered in detail: California and Bavaria (1995 and 2000), Wisconsin and Bavaria (1998), Maryland and Schleswig-Holstein (2002) and California and North Rhine-Westphalia (2004). Taken together, these examples provide important insights into the ways in which multi-level governance structures allow subnational actors to shape policy developments around global environmental issues. This timely study - the first of its kind on this topic - will appeal to both academic researchers and policymakers with an interest in global environmental governance, environmental policymaking, comparative governance and the roles of individuals versus institutions.
1. Introduction -- 2. Analyzing transnational partnerships : theoretical frameworks -- 3. The road to the partnerships : a historical background -- 4. California and Bavaria (1995) -- 5. Wisconsin and Bavaria (1998) -- 6. California and Bavaria (2000) -- 7. Maryland and Schleswig-Holstein (2002) -- 8. California and North Rhine-Westphalia (2004) -- 9. Analysis and implications.
Includes bibliographical references and index.
Keywords: Sustainable development -- Government policy; Sustainable development -- United States -- International cooperation; Sustainable development -- Germany -- International cooperation; Electronic books